Corrosion behavior of deformed steel for automobile parts in various environments - Abd. Karim, Mohd. Fauzi (2008)
Corrosion behavior of three types of deformed steel sheets of automobile part have been studied as a function of shapes namely flat and curved. Three different solutions were chosen; chloride, phosphate and carbonate for the corrosion tests. A correlation between the shapes, types and environments to corrosion protection were established by employing electrochemical test using potentiodynamic polarization. Cyclic corrosion test was also performed as comparison to the electrochemical test. An almost consistent correlation was found to exist between specimen shapes and corrosion rate depends on types and exposure environments. Generally, as received samples showed the highest corrosion rate for JSC 270F type while flat shape showed the highest corrosion rate for JAC 270F and curved shape showed the highest corrosion rate for JSH 370W in all environments respectively. On the other hand phosphate solution was found to be the most corrosive environment to these three types of automobile parts.